Supporting Development of Tourism by Local Municipal Self-Governments within the Naturally Valuable Areas of the Lubelskie Voivodship - Danuta Guzal-Dec (Barometr Regionalny)
The aim of the work is to diagnose the activity of local governments in supporting tourism development in naturally valuable areas of the Lubelskie Voivodship (Poland ). The study area consisted of 30 municipalities with the highest natural value in the Lubelskie Voivodship selected for the study based on the value of the indicator developed by D. Guzal-Dec in the study of the natural value of rural and urban-rural communes within the Lubelskie Voivodship. A questionnaire interview was used for the diagnostic purposes of the survey. Interviews were completed in 2013. The research material comprised 30 interviews with mayors and staff dealing with environmental issues in municipal offices. Websites of the surveyed communes were an important source of information. In the surveyed group, approximately 75% of the authorities declared their preference for tourism as the main direction of development of their commune. Detailed analysis of the use of various instruments of support lead to the conclusion that about 50% of them actively support tourism, of which about 30% have a planned policy manifested in a comprehensive application of the instruments of support. It seems, therefore, that strategies of cooperation for the development of tourism should be systematically and rationally utilized, especially in communities with high natural potential and less favorable non-natural conditions for tourism development.